Energy Management System for Three-Phase Microgrids using Affine Arithmetic - Moran, John Penaloza [UNESP]; Lopez, Julio C.; Feltrin, Antonio Padilha [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This work presents a three-phase mathematical model based on Affine Arithmetic to solve the problem of the Energy Management System for microgrids in grid-connected mode, considering the uncertainties in the load and renewable energy. The resulting model contains two optimization subproblems. The first problem is a mixed-integer linear programming model that represents the Unit Commitment problem based on Affine Arithmetic, and the second problem is a non-linear programming model that establishes the formulation for the economic dispatch problem. The optimization problems are written in AMPL, while the heuristic process, which integrates the subproblems, is solved in Matlab2018b through the AMPL-API interface. Finally, the efficiency of the proposed work is evaluated in a three-phase IEEE 19-bus system, where the results showed robust solutions without requiring a considerable computational effort, reaching an economical operation.
Keywords: affine arithmetic; distributed generation; energy management system; microgrids; uncertainties